2005
DOI: 10.1162/089892905774597227
|View full text |Cite
|
Sign up to set email alerts
|

Left Auditory Cortex and Amygdala, but Right Insula Dominance for Human Laughing and Crying

Abstract: Evidence suggests that in animals their own species-specific communication sounds are processed predominantly in the left hemisphere. In contrast, processing linguistic aspects of human speech involves the left hemisphere, whereas processing some prosodic aspects of speech as well as other not yet well-defined attributes of human voices predominantly involves the right hemisphere. This leaves open the question of hemispheric processing of universal (species-specific) human vocalizations that are more directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 52 publications
(54 reference statements)
10
51
2
1
Order By: Relevance
“…Although we cannot provide a direct link between the recorded neurons and the perception or a behavioral reaction of the animal, human studies strongly suggest such a link (Augustine, 1996;Bamiou et al, 2003;Hickok and Poeppel, 2007). In fact, human studies not only show that the insula is activated by different forms of speech (Zatorre et al, 1994;Rumsey et al, 1997;Meyer et al, 2002;Kotz et al, 2003;Brown et al, 2004;Wong et al, 2004;Sander and Scheich, 2005), but evidence from patients also makes the case for a causal role of the insula in phonological processing. Subjects with dyslexia, for example, of- ten exhibit lower insula activation in different phonological tasks (Paulesu et al, 1996;Cornette et al, 1998), and many individuals with strokes or ischemic infarcts near the insula show deficits in acoustic or language perception (Cancelliere and Kertesz, 1990;Habib et al, 1995).…”
Section: An Auditory Region In the Insulamentioning
confidence: 68%
See 1 more Smart Citation
“…Although we cannot provide a direct link between the recorded neurons and the perception or a behavioral reaction of the animal, human studies strongly suggest such a link (Augustine, 1996;Bamiou et al, 2003;Hickok and Poeppel, 2007). In fact, human studies not only show that the insula is activated by different forms of speech (Zatorre et al, 1994;Rumsey et al, 1997;Meyer et al, 2002;Kotz et al, 2003;Brown et al, 2004;Wong et al, 2004;Sander and Scheich, 2005), but evidence from patients also makes the case for a causal role of the insula in phonological processing. Subjects with dyslexia, for example, of- ten exhibit lower insula activation in different phonological tasks (Paulesu et al, 1996;Cornette et al, 1998), and many individuals with strokes or ischemic infarcts near the insula show deficits in acoustic or language perception (Cancelliere and Kertesz, 1990;Habib et al, 1995).…”
Section: An Auditory Region In the Insulamentioning
confidence: 68%
“…Imaging studies implicate the insula in processing simple sounds and rhythms (Griffiths et al, 1997;Herdener et al, 2008) and vocal communication signals (Zatorre et al, 1994;Rumsey et al, 1997;Meyer et al, 2002;Kotz et al, 2003;Wong et al, 2004;Sander and Scheich, 2005) (and see Augustine, 1985;Bamiou et al, 2003). In addition, insula lesions often manifest as deficits in sound or speech recognition (auditory agnosia) and speech production (Spreen et al, 1965;Cancelliere and Kertesz, 1990;Engelien et al, 1995;Habib et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the neuroimaging literature, there is evidence that vocalizations predominantly activate the amygdala and other subcortical structures (Fecteau et al, 2007;Phillips et al, 1998;Sander & Scheich, 2005;Szameitat et al, 2010), whereas this evidence is less consistent for emotional prosody (Wiethoff et al, 2009). On the basis that vocalizations selectively trigger limbically-dominated processes that form part of the ancestral subcortical system for regulating emotional responses (e.g., Frühholz, Trost, & Grandjean, 2014;Jürgens, NOT THE FINAL VERSION Meyer et al, 2007;Sander & Scheich, 2005), activation of this circuitry would strengthen input used to tag the urgency and biological salience of vocal expressions to listeners by dedicated temporo-frontal cortical mechanisms that process voice information (Belin et al, 2000;Schirmer & Kotz, 2006;Schwartz & Kotz, 2013). In terms of the time course of emotion processing, our data show that this leads to preferential deployment of attention to the type and quality of different vocal signals in the 100-200ms time window, even when vocal stimuli are not the subject of attentional focus (Aschliemann et al, 2008;Fecteau et al, 2004;Gädeke et al, 2013).…”
Section: Neurocognitive Mechanisms For Processing Emotion In and Out mentioning
confidence: 99%
“…The nuclei of the amygdala structure are crucial in this neural network (Bach et al, 2008b;Ethofer et al, 2009;Fecteau et al, 2007;Frühholz and Grandjean, 2013;Grandjean et al, 2005;Leitman et al, 2010;Phillips et al, 1998;Sander et al, 2003aSander et al, , 2007Sander and Scheich, 2005;Wiethoff et al, 2009). While their functional roles are still debated in terms of whether they can truly decode the emotional valence of vocal expressions or the extent to which they are involved in emotional responses to emotional vocalizations (Adolphs and Tranel, 1999;Bach et al, 2013;Scott et al, 1997;Sprengelmeyer et al, 1999), the nuclei of the amygdala are sensitive to vocal cues of anger (Bach et al, 2008a), as well as to expressions of happiness (Fecteau et al, 2007;Leitman et al, 2010;Sander et al, 2003b;Sander and Scheich, 2005), suggesting a response to high arousal states in general (Frühholz et al, 2014), as has also been suggested in the domain of olfaction (Anderson et al, 2003). The hippocampus is another large subcortical structure of the so-called limbic system that appears to have a role in the decoding of emotions, in particular with respect to memory processes (Frühholz et al, 2014;Maguire, 2001).…”
Section: Brain Mechanisms Involved In Emotional Processing In Primatesmentioning
confidence: 99%